THEORETICAL ANALYSIS OF ENERGY PROCESSES IN MUTUAL LOAD ELECTRIC TRACTION DC MACHINES - Afanasov, A. M. (Science and Transport Progress, 2008)
The analysis of power streams in the schemes of mutual loading of hauling electric machines of direct and pulsating current is presented.